He's Semi-inverse Method for Camassa-Holm Equation and Simplied Modied Camassa-Holm Equation - Najafi, Malihe; Arbabi, Somayeh; Najafi, Mohammad (International Journal of Physical Research, 2013)
In this Letter, we study Camassa-Holm equation and Simpli?ed Modi?ed Camassa-Holm equation by using the well-known He’s Semi-inverse Method. The solitary solutions are obtained using the Ritz method. In fact, the He’s Semi-inverse Method is a promising method to various systems of linear and nonlinear equations.